Opini Sumpah Hipokrates di Era Digital: Perlukah Diubah? - Sidhi Laksono (Jurnal Hukum dan Etika Kesehatan, 2022)
The Hippocratic Oath (HO) is an oath recited by all doctors in the world. HO contains a promise based on ethical principles and medical practice. Adherence to the principles in HO must be upheld by every medical practitioner. However, with the rapid development of the current era, HO is no longer appropriate. Such as the advancement of digital health, the use of artificial intelligence (AI), the assessment of big data in healthcare, the security of digital patient data, patient-based care, and the role of patients in determining the direction of self-medication and health digital virtual services. This transformation demands a change in the general context of HO. This article will briefly discuss about HO in relation to changes in the digital era. Some of HO's inputs on the progress of the digital world today include the use of digital technology in medical practice, the role of patients, patient data privacy, and the use of big data. This article uses a literature review research method with an ethical approach.